2018
DOI: 10.2147/dddt.s172612
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of Nrf2 modulators for cancer chemoprevention and therapy: a review

Abstract: A major cell defense mechanism against oxidative and xenobiotic stress is mediated by the Nrf2/Keap1 signaling pathway. The Nrf2/Keap1 pathway regulates gene expression of many cytoprotective and detoxifying enzymes, thus playing a pivotal role in maintaining redox cellular homeostasis. Many diseases including cancer have been closely related to impaired Nrf2 activity. Targeting Nrf2 and modulating its activity represents a novel modern strategy for cancer chemoprevention and therapy. In this review, different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
91
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 132 publications
(190 reference statements)
0
91
0
2
Order By: Relevance
“…Such a process allows Keap1 to recognize ARE initiation transcription. [7] Intracellular endogenous antioxidant gene, such as quinone oxidoreductase-1 (NQO1), [8] superoxide dismutase (SOD), heme oxygenase-1 (HO-1), [8] glutathione s-transferases (GST), and γ-glutamylcysteine synthetase (γ-GCS) also called glutamate cysteine ligase (GCL), catalase(CAT), etc., are increased to maintain homeostasis. [9] The protein encoded by the Nrf2-target gene has a wide range of cytoprotective effects including antioxidation, detoxification, and anti-inflammatory.…”
Section: Introductionmentioning
confidence: 99%
“…Such a process allows Keap1 to recognize ARE initiation transcription. [7] Intracellular endogenous antioxidant gene, such as quinone oxidoreductase-1 (NQO1), [8] superoxide dismutase (SOD), heme oxygenase-1 (HO-1), [8] glutathione s-transferases (GST), and γ-glutamylcysteine synthetase (γ-GCS) also called glutamate cysteine ligase (GCL), catalase(CAT), etc., are increased to maintain homeostasis. [9] The protein encoded by the Nrf2-target gene has a wide range of cytoprotective effects including antioxidation, detoxification, and anti-inflammatory.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, there is great interest in pharmacological modulators of Nrf2 that could be developed into therapeutics for the treatment and prevention of disease (Buendia et al, ; Cuadrado et al, ; Dodson et al, ; Du et al, ; Gacesa et al, ; Kumar, Kim, More, Kim, & Choi, ; Lu, Ji, Jiang, & You, ; Rabbani, Ellison, et al, ; Sivandzade et al, ; Sklirou, Papanagnou, Fokialakis, & Trougakos, ; Sova & Saso, ; Vega, Dodson, Chapman, & Zhang, ; Yamamoto et al, ; Zhang et al, ), including skin disorders (Dodson et al, ; Ferrándiz, Nacher‐Juan, & Alcaraz, ; Gacesa et al, ; Kumar et al, ; Lu et al, ; Penta, Somashekar, & Meeran, ; Rabbani, Ellison, et al, ; Son et al, ; Yamamoto et al, ). Examples of natural products known to induce epigenetic Nrf2‐activating effects are shown in Figure (Bambouskova et al, ; Dodson et al, ; Fazzari et al, ; Fratantonio et al, ; Garaude, ; Gill, Raman, Yost, Garrett, & Vedam‐Mai, ; Gu et al, ; Iranshahy, Iranshahi, Abtahi, & Karimi, ; Irwin, Moos, Faller, Steliou, & Pinkert, ; Kumar et al, ; Li et al, ; Mathers et al, ; Matzinger, Fischhuber, & Heiss, ; Moos, Maneta, et al, ; Moos et al, ; Rigacci & Stefani, ; Rusu, Gheldiu, Mocan, Vlase, & Popa, ; Sivandzade et al, ; Steliou, Boosalis, Perrine, Sangerman, & Faller, ; Steliou, Faller, Pinkert, Irwin, & Moos, ; Tsujita et al, ).…”
Section: Nrf2‐activating Therapeuticsmentioning
confidence: 99%
“…In an attempt to overcome clinical and pharmacological shortfalls, such as efficacy and/or safety issues associated with stochastic off‐target adverse effects that were exposed in clinical trials (Dodson et al, ; Patra, Mukhopadhyay, Sarkar, Mukherjee, & Chawla‐Sarkar, ; Sova & Saso, ), a wide array of synthetic and semisynthetic Nrf2‐modulators were prepared (Deck, Whalen, Hunsaker, Royer, & Jagt, ; Sivandzade et al, ; Sklirou et al, ; Sova & Saso, ). Three notable examples of synthetic Nrf2‐activating compounds that advanced to clinical trials are shown in Figure (Cuadrado et al, ; Gacesa et al, ; Naidu et al, ; Patra et al, ; Rabbani, Ellison, et al, ; Sklirou et al, ; Sova & Saso, ).…”
Section: Nrf2‐activating Therapeuticsmentioning
confidence: 99%
See 2 more Smart Citations